Soziale Arbeit in der Corona-Pandemie: Zwischen Überforderung und Marginalisierung. Empirische Trends und professionstheoretische Analysen zur Arbeitssituation im Lockdown - Nikolaus Meyer; Christina Buschle (IUBH Internationale Hochschule, 2020)
– The corona pandemic, but also contact restrictions and other hygiene measures have significantly changed the actions and routines of social work workers. The first trends from the quantitative study on the work situation in social work during the corona pandemic are now available. It is already becoming apparent: In addition to the concentration of work, employees perceive changed work alliances with the addressees as well as changed professional standards. Despite higher demands, however, social recognition remains low. At present it is still open what consequences the changes in occupational standards will have for professional action in social work in the future.
Keywords: 300; Corona-Pandemie; Covid-19; Soziale Folgen; Gesellschaftliche Anerkennung; Professionalisierung; Professionalität; Soziale Arbeit